Microcrystalline Cellulose Isolated from Rami (Boehmeria nivea L. Gaud) used as a Disintegrant in Dimenhydrinate Tablets - Nagina Gulab Belali; Anis Y. Chaerunisaa; Taofik Rusdiana (Indonesian Journal of Pharmaceutics, 2020)
Microcrystalline cellulose was isolated from rami (Boehmeria Nivea L. Gaud), and applied as disintegrant in tablets of dimenhydrinate, made by direct compression and wet granulation. The aim of this study is to produce dimenhydrinate tablets with Microcrystalline Cellulose Rami (MCC Rami) isolated from Rami (Boehmeria Nivea L. Gaud), as a disintegrant and assess the effect of MCC Rami and Granulation technique on physical properties of drug such as, disintegration time, drug release and dissolution. Formulations of dimenhydrinate 100mg tablets were prepared with a combination of mannitol and lactose as a filler and MCC Rami as disintegrant in a concentration of 10-20%. The formulas were directly compressed or were compressed into tablets after wet granulation. The mechanical properties, drug release, physical properties and effects of process parameters, methods of applying disintegrant in tablet formulas were examined. A significant difference in disintegration time of tablets that were produced by direct compression and wet granulation was seen, that can be attributed to the porous structure of granules that enhanced fast disintegration, which had eventually improved dissolution and drug release. F1 and F2 with MCC Rami and physical mixture of MCC Rami with crosspovidone as a disintegrant that were directly compressed disintegrated in 79 and 72 seconds respectively thats not a significant difference, however when MCC was applied in an intragranular way its disintegration time is 67 seconds. The results showed that the method of disintegrant application and press of tableting has a significant effect on drug release and dissolution.Keywords : Microcrystalline Cellulose, wet granulation, disintegrant, Boehmeria Nivea L. Gaud.